2023
DOI: 10.1364/optcon.480593
|View full text |Cite
|
Sign up to set email alerts
|

Dysprosium gain-switched fiber laser at 3.24 µm pumped at 1064 nm

Abstract: We report a dysprosium-doped gain switched fluoride fiber laser pumped at 1064 nm and emitting at 3244 nm. Pulses with energies up to 1  µJ were generated on a wide range of repetition rates between 100 kHz and 200 kHz, the highest reported for a pulsed dysprosium-doped fiber laser, producing an average output power reaching 207 mW. Stable 8.9  µJ pulses were also generated near 10 kHz, which is the highest pulse energy reported to date from a 1.1 µm band pumped dysprosium-doped fiber laser. This shows the 1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Pajewski et al and Luo et al fabricated a gain-switched Dy 3+ -doped ZBLAN fiber laser [18,19]. Recently, Jobin et al reported a 3.24 µm gain-switched fiber laser pumped by 1064 nm [20].…”
Section: Introductionmentioning
confidence: 99%
“…Pajewski et al and Luo et al fabricated a gain-switched Dy 3+ -doped ZBLAN fiber laser [18,19]. Recently, Jobin et al reported a 3.24 µm gain-switched fiber laser pumped by 1064 nm [20].…”
Section: Introductionmentioning
confidence: 99%
“…In that work, Dy−doped multi-component phosphate core glass fiber was successfully drawn by using a rod-in-tube method. Fluoride fibers have been recently employed to build novel Mid-IR sources as well [21], [22]. Furthermore, in [23], another Dy−doped NaLa(WO 4 ) 2 glass ceramic fiber with good uniformity was fabricated using the molten core method showing that it can be a very promising material candidate for tunable yellow lasers [23].…”
Section: Introductionmentioning
confidence: 99%